A new genus of Stenetriidae Hansen, 1905 (Asellota: Isopoda: Crustacea) from the Great Barrier Reef, Australia and the southwestern Pacific - Bruce, Niel L.; Cumming, R. L. (Zootaxa, 2015)
Onychatrium gen. nov. is described, with five included species: Onychatrium forceps sp. nov., the type species and Onychatrium torosus sp. nov., both from the Great Barrier Reef; Onychatrium entale (Nordenstam, 1946) comb. nov., from Tapateuen (= Tabiteue Island), Gilbert Islands; Onychatrium thomasi (Bolstad & Kensley, 1999) comb. nov., from Madang, Papua New Guinea; and Onychatrium echiurum (Nobili, 1906) comb. nov., and species inquirenda from the Tumaotu Islands, Eastern French Polynesia. The primary distinguishing characters for Onychatrium gen. nov. are a trapezoid pseudosrostrum, the male pereopod 1 with elongate dactylus (4.7–7.3 as long as proximal width), propodus with strongly produced and acute lobe, carpus with a distally acute, flat, ventrally directed process (except O. torosus sp. nov., which has a short and truncate process) and the merus with a distally directed inferodistal lobe. The genus is known only from the southern Pacific, from the Tuamotus (eastern French Polynesia) to the Great Barrier Reef and northern Papua New Guinea.